2014
DOI: 10.1093/molbev/msu230
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide SNP Analysis Reveals Population Structure and Demographic History of the Ryukyu Islanders in the Southern Part of the Japanese Archipelago

Abstract: The Ryukyu Islands are located to the southwest of the Japanese archipelago. Archaeological evidence has revealed the existence of prehistoric cultural differentiation between the northern Ryukyu islands of Amami and Okinawa, and the southern Ryukyu islands of Miyako and Yaeyama. To examine a genetic subdivision in the Ryukyu Islands, we conducted genome-wide single nucleotide polymorphism typing of inhabitants from the Okinawa Islands, the Miyako Islands, and the Yaeyama Islands. Principal component and clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 44 publications
6
58
0
Order By: Relevance
“…A possible explanation would be some unknown populations were involved in the formation of Ryukyuans, as previously suggested. 24 We identified eight Ainu individuals who might be recently admixed with Mainland Japanese based on their intermediate positions between Ainu and Mainland Japanese clusters in the PCA plot (Supplementary Figure 3). If these individuals were the result of very recent admixture events, then one of the pair of chromosomes should be from an Ainu parent and the other from a Mainland Japanese parent.…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation would be some unknown populations were involved in the formation of Ryukyuans, as previously suggested. 24 We identified eight Ainu individuals who might be recently admixed with Mainland Japanese based on their intermediate positions between Ainu and Mainland Japanese clusters in the PCA plot (Supplementary Figure 3). If these individuals were the result of very recent admixture events, then one of the pair of chromosomes should be from an Ainu parent and the other from a Mainland Japanese parent.…”
Section: Resultsmentioning
confidence: 99%
“…Previous genetic studies mostly focused on individuals from Okinawa Island and found that they have high genetic similarities with the Ainu in Hokkaido, even though these two groups are geographically very distant (Omoto, 1995;Omoto and Saitou, 1997). Genome-wide SNP studies show that the Okinawans form a distinct cluster from the Hondo Japanese (Yamaguchi-Kabata et al, 2008), while a more detailed genetic survey of individuals from three main islands in the Ryukyu cluster found differentiation between the island groups that was attributed to genetic drift (Sato et al, 2014).…”
Section: The Indigenous Groups Of Japanmentioning
confidence: 99%
“…Dental morphology may affect facial morphology, and three polymorphisms in three genes-ectodysplasin A receptor (EDAR), wingless-type MMTV integration site family, member 10A (WNT10A), and paired box 9 (PAX9)-can affect tooth size and non-metric dental traits (Kimura et al, 2009(Kimura et al, , 2015Lee et al, 2012;Park et al, 2012). Recent population genomics studies have demonstrated a clear genetic differentiation between Ryukyuans and mainland Japanese (Yamaguchi-Kabata et al, 2008;HUGO Pan-Asian SNP Consortium, 2009;Sato et al, 2014), and a nonsynonymous SNP in EDAR is especially differentiated between the two populations. Therefore, this polymorphism may be a strong candidate for a causal gene responsible for morphological differences between Ryukyuan and mainland Japanese faces.…”
Section: Genetic and Environmental Factorsmentioning
confidence: 99%
“…Therefore, physical anthropologists have proposed that the origin of the modern Japanese people has a dual structure; specifically, they have proposed that Jomon hunter-gatherers were the native inhabitants of the Japanese archipelago, and migrations of Yayoi farmers resulted in admixture between the two populations with the proportions of admixture varying among local regions (Hanihara, 1991). This model has been supported by genetic studies (Omoto and Saitou, 1997;Yamaguchi-Kabata et al, 2008;HUGO Pan-Asian SNP Consortium, 2009;Jinam et al, 2012;Koganebuchi et al, 2012;Sato et al, 2014).…”
Section: Introductionmentioning
confidence: 99%